2022
DOI: 10.3390/ijms231710029
|View full text |Cite
|
Sign up to set email alerts
|

Novel Short PEG Chain-Substituted Porphyrins: Synthesis, Photochemistry, and In Vitro Photodynamic Activity against Cancer Cells

Abstract: This work presents the synthesis and characterization of metal-free, zinc (II), and cobalt (II) porphyrins substituted with short PEG chains. The synthesized compounds were characterized by UV-Vis, 1H and 13C NMR spectroscopy, and MALDI-TOF mass spectrometry. The origin of the absorption bands for tested compounds in the UV-Vis range was determined using a computational model based on the electron density functional theory (DFT) and its time-dependent variant (TD-DFT). The photosensitizing activity was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…It was documented in previous studies that paclitaxel bound to the microtubule at the taxoid site on the luminal face of β-tubulin and maintained the stability and destroyed the dynamics of the microtubule, thus leading to mitotic catastrophe [ 33 ]. However, according to the “similarity principle” [ 34 ], our 2,5-DKPs might have the same mechanism as plinabulin or its analogs, which acted as a tubulin binder near or at the colchicine binding site located at the interfacial region of the α- and β-tubulin studied using photoaffinity labeling [ 35 , 36 ] or computational modeling [ 37 , 38 , 39 , 40 ], leading to the inhibition of tubulin polymerization and the prevention of microtubule formation, thus resulting in the apoptosis of cancer cells. The detailed mechanism will be investigated in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…It was documented in previous studies that paclitaxel bound to the microtubule at the taxoid site on the luminal face of β-tubulin and maintained the stability and destroyed the dynamics of the microtubule, thus leading to mitotic catastrophe [ 33 ]. However, according to the “similarity principle” [ 34 ], our 2,5-DKPs might have the same mechanism as plinabulin or its analogs, which acted as a tubulin binder near or at the colchicine binding site located at the interfacial region of the α- and β-tubulin studied using photoaffinity labeling [ 35 , 36 ] or computational modeling [ 37 , 38 , 39 , 40 ], leading to the inhibition of tubulin polymerization and the prevention of microtubule formation, thus resulting in the apoptosis of cancer cells. The detailed mechanism will be investigated in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the investigators testified that only in the presence of GSH and hydrogen sulfide occurs the photosensitizing agent activation by the quenching group departure, stating that it has a high clinical potential in reducing the effect of cutaneous photosensitivity; Improvement of functional properties of this family of PSs: Certain functional groups can significantly contribute to refining physiological and chemical stability and biocompatibility [ 148 ]. The introduction of polyethylene glycol (PEG) moieties into porphyrin cores, for example, has been reported several times in the literature [ 149 , 150 , 151 ]. Lazewski et al [ 151 ] demonstrated that, irrespective of the coordinated metal, short-PEGylated porphyrins reveal reduced dark cytotoxicity, increased ability to produce singlet oxygen, and that the structural location where the polymer is introduced can result in the variation of the biological effects; As an interface between single-PSs and nano-PSs, Li et al [ 152 ] demonstrate that the chain conjugation of PEG-bearing porphyrins with perylene diimide units resulted, by self-assembly, in a kind of nanoparticle with attractive properties: (i) high biocompatibility; (ii) intense absorption in the visible and NIR regions; (iii) therapeutic efficiency in vitro and in vivo with reduced side effects; (iv) potential use as a theranostic agent by obtaining second near-infrared (NIR-II) fluorescence images.…”
Section: N -Heterocyclic-bearing Dyes As Photodynamic Therap...mentioning
confidence: 99%
“…Improvement of functional properties of this family of PSs: Certain functional groups can significantly contribute to refining physiological and chemical stability and biocompatibility [ 148 ]. The introduction of polyethylene glycol (PEG) moieties into porphyrin cores, for example, has been reported several times in the literature [ 149 , 150 , 151 ]. Lazewski et al [ 151 ] demonstrated that, irrespective of the coordinated metal, short-PEGylated porphyrins reveal reduced dark cytotoxicity, increased ability to produce singlet oxygen, and that the structural location where the polymer is introduced can result in the variation of the biological effects;…”
Section: N -Heterocyclic-bearing Dyes As Photodynamic Therap...mentioning
confidence: 99%
See 2 more Smart Citations